Hybrid Work and Digital Leadership on Employee Performance through Work-Life Balance in Startups in Indonesia - Yuli Maharani; Anwar Azazi; Efa Irdhayanti; Ilzar Daud; Ahmad Shalahuddin (Journal of Educational Management Research, 2026)
This study aims to examine the effect of hybrid work and digital leadership style on employee performance, with work-life balance as a mediating variable in technology startup environments. A quantitative explanatory design was applied to test the proposed relationships among variables. Data were collected through surveys of 200 employees working in hybrid-based technology startups across Java. The analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect effects between constructs. The results indicate that hybrid work has no significant direct effect on employee performance, while digital leadership shows a significant positive effect on performance improvement. Both hybrid work and digital leadership significantly enhance work-life balance among employees. Furthermore, work-life balance positively influences employee performance and functions as a full mediator in the relationship between hybrid work and performance, and as a partial mediator between digital leadership and performance. These findings highlight the importance of balancing work arrangements and leadership practices to optimize employee outcomes in digital startup ecosystems.